Molecular evidence supports simultaneous association of the achlorophyllous orchid Chamaegastrodia inverta with ectomycorrhizal Ceratobasidiaceae and Russulaceae - Lorenzo Pecoraro; Xiao Wang; Giuseppe Venturella; Wenyuan Gao; Tingchi Wen; Yusufjon Gafforov; Vijai Kumar Gupta (BMC Microbiology, 2020)
Abstract Background Achlorophyllous orchids are mycoheterotrophic plants, which lack photosynthetic ability and associate with fungi to acquire carbon from different environmental sources. In tropical latitudes, achlorophyllous forest orchids show a preference to establish mycorrhizal relationships with saprotrophic fungi. However, a few of them have been recently found to associate with ectomycorrhizal fungi and there is still much to be learned about the identity of fungi associated with tropical orchids. The present study focused on mycorrhizal diversity in the achlorophyllous orchid C. inverta, an endangered species, which is endemic to southern China. The aim of this work was to identify the main mycorrhizal partners of C. inverta in different plant life stages, by means of morphological and molecular methods. Results Microscopy showed that the roots of analysed C. inverta samples were extensively colonized by fungal hyphae forming pelotons in root cortical cells. Fungal ITS regions were amplified by polymerase chain reaction, from DNA extracted from fungal mycelia isolated from orchid root samples, as well as from total root DNA. Molecular sequencing and phylogenetic analyses showed that the investigated orchid primarily associated with ectomycorrhizal fungi belonging to a narrow clade within the family Ceratobasidiaceae, which was previously detected in a few fully mycoheterotrophic orchids and was also found to show ectomycorrhizal capability on trees and shrubs. Russulaceae fungal symbionts, showing high similarity with members of the ectomycorrhizal genus Russula, were also identified from the roots of C. inverta, at young seedling stage. Ascomycetous fungi including Chaetomium, Diaporthe, Leptodontidium, and Phomopsis genera, and zygomycetes in the genus Mortierella were obtained from orchid root isolated strains with unclear functional role. Conclusions This study represents the first assessment of root fungal diversity in the rare, cryptic and narrowly distributed Chinese orchid C. inverta. Our results provide new insights on the spectrum of orchid-fungus symbiosis suggesting an unprecedented mixed association between the studied achlorophyllous forest orchid and ectomycorrhizal fungi belonging to Ceratobasidiaceae and Russulaceae. Ceratobasidioid fungi as dominant associates in the roots of C. inverta represent a new record of the rare association between the identified fungal group and fully mycoheterotrophic orchids in nature.